2021
DOI: 10.1186/s12933-021-01334-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related disparities in the incidence and outcomes of hemorrhagic stroke among type 2 diabetes patients: a propensity score matching analysis using the Spanish National Hospital Discharge Database for the period 2016–18

Abstract: Background To analyze incidence, use of therapeutic procedures, use of oral anticoagulants (OACs) and antiplatelet agents prior to hospitalization, and in-hospital outcomes among patients who were hospitalized with hemorrhagic stroke (HS) according to the presence of type 2 diabetes mellitus (T2DM) in Spain (2016–2018) and to assess the role of sex differences among those with T2DM. Methods Using the Spanish National Hospital Discharge Database we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
(165 reference statements)
1
3
0
Order By: Relevance
“…Is remarkable that in a previous study conducted by our group, among T2DM patients who had experienced a hemorrhagic stroke, similar sex differences were detected, finding that men presented higher incidence rates, more frequent decompressive craniectomy, and lower in-hospital mortality than women [ 44 ].…”
Section: Discussionsupporting
confidence: 72%
“…Is remarkable that in a previous study conducted by our group, among T2DM patients who had experienced a hemorrhagic stroke, similar sex differences were detected, finding that men presented higher incidence rates, more frequent decompressive craniectomy, and lower in-hospital mortality than women [ 44 ].…”
Section: Discussionsupporting
confidence: 72%
“…These epide-miologic studies demonstrated that diabetes is an independent risk factor for stroke. 5,[14][15][16][17][18][19][20][21][22][23][24] Furthermore, the risk of stroke is higher in people with either type 1 diabetes (T1D) (HR: 1.50; 95% CI: 1.23-1.83) or type 2 diabetes (T2D; HR: 1.76; 95% CI: 1.65-1.87) compared with people without diabetes. 14 There are also differences in risk according to the stroke type.…”
Section: Diabetes As a Risk Factor For Strokementioning
confidence: 99%
“…16 However, other studies have reported contradictory findings regarding sex differences in the risk of stroke associated with diabetes when analyzing specific age groups or stroke types (Figure 1). 15,17,22 In addition to diabetes, prediabetes-defined by the American Diabetes Association (ADA) as impaired fasting glucose (fasting plasma glucose 100-125 mg/dL [5.6-6.9 mmol/L]) and/or impaired glucose tolerance (plasma glucose levels 2 hours after 75 g of oral glucose intake of 140-199 mg/dL [7.8-11.0 mmol/L]) and/or glycated hemoglobin (HbA1c) 5.7%-6.4% (39-47 mmol/L) 25 -may be associated with a modestly higher risk of future stroke compared with those with normal glycemia. 26 Moreover, the duration of diabetes is independently associated with the risk of ischemic stroke; the risk has been reported to increase by 3% each year and triples in those who have had diabetes for ≥10 years, compared with those without diabetes.…”
Section: Diabetes As a Risk Factor For Strokementioning
confidence: 99%
See 1 more Smart Citation